Characteristics of post orgasmic illnes syndrome (POIS) in men - Campos Rivero, Oscar Alberto (2024)
Post-orgasmic illness syndrome is a rare disease characterized by various symptoms that appear shortly after ejaculation and can last up to 7 days. In addition to medical symptoms, psychological symptoms have also been identified, which negatively affect the lives of men and their partners by limiting their romantic relationships, erotic behaviors and, therefore, their sexual relationships. Since this syndrome is recent, it is suggested that studies be carried out and that cases be monitored and adequately treated, given that it not only affects health, but also psychological, social and sexual aspects of patients.